Efficacy and limitations of diffusion-weighted imaging with background suppression-based whole-body magnetic resonance imaging in high-risk prostate cancer staging: A retrospective study - Nobuyuki Nakajima; Toshiki Kazama; Taro Takahara; Kazuya Oda; Takahiro Ogawa; Meiko Aoki; Sena Ono; Jun Naruse; Kumpei Takahashi; Soichiro Yuzuriha; Tatsuya Otaki; Tatsuya Umemoto; et al. (PLoS ONE, 2026)
Purpose To evaluate the diagnostic performance and limitations of whole-body magnetic resonance imaging (WB-MRI) using diffusion-weighted imaging with background body signal suppression (DWIBS) for staging high-risk prostate cancer (PCa) in comparison with conventional computed tomography (CT) and bone scintigraphy (BS). Materials and methods This retrospective study included 38 patients with newly diagnosed high-risk PCa who underwent CT, bone scintigraphy (BS), and DWIBS, all performed within two months prior to treatment initiation. DWIBS was performed with coverage from the skull base to the proximal femur. Pathological findings from extended pelvic lymph node dissection were available in 14 patients and were used as the reference standard for lymph node metastasis. For all remaining cases and metastatic sites, the reference standard was established by the best valuable comparator consensus of two radiologists and two urologists using imaging and clinical follow-up data. Results For lymph node metastases, both DWIBS and CT demonstrated a sensitivity of 64.3% and a specificity of 100.0%. For bone metastases, DWIBS showed a sensitivity of 88.9% and specificity of 100.0%, whereas BS showed a sensitivity of 100.0% and a specificity of 96.6%. Lung metastases were observed in three patients. Chest CT detected all lesions, whereas DWIBS detected two cases; these were confirmed on coronal T2-weighted images but not visualized on diffusion-weighted imaging alone. Conclusion DWIBS demonstrated acceptable diagnostic performance for staging high-risk PCa, comparable to CT and BS, while offering the advantage of radiation-free WB-MRI and avoidance of radioisotopes. When combined with chest CT, this approach may represent a practical and feasible alternative imaging strategy for initial PCa staging.